2011
DOI: 10.1007/s10096-011-1391-y
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a whole-system approach in an antimicrobial stewardship programme at the Singapore General Hospital

Abstract: Inappropriate antibiotic use contributes to antimicrobial resistance. Multi-faceted antimicrobial stewardship programmes (ASPs) are recommended for sustainable changes in prescribing practices. A multi-disciplinary ASP was established in October 2008 and piloted in the Departments of General Surgery, Renal Medicine and Endocrinology sequentially. To improve the quality of patient care via optimising the (1) choice, (2) dose, (3) route and (4) duration of antibiotics, a "whole-system" approach incorporating pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 20 publications
3
41
0
5
Order By: Relevance
“…Specific strategies for success are required in different settings [5,30]. Adherence to antibiotic recommendations can decrease the number of doses of intravenous medication and length of stay, both of which reduce the cost of the hospitalization without adverse effects to the patients [13,[31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…Specific strategies for success are required in different settings [5,30]. Adherence to antibiotic recommendations can decrease the number of doses of intravenous medication and length of stay, both of which reduce the cost of the hospitalization without adverse effects to the patients [13,[31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…Although measurement of non-targeted or total antimicrobials is more labor intensive than measuring targeted agents alone, this information is essential to allow for the detection of compensatory increases in the use of other agents, which can lead to the "squeezing the balloon" phenomenon [79]. However, some studies only reported consumption of targeted antimicrobials [8,20,30,44,54,75].…”
Section: Metrics Process Measuresmentioning
confidence: 98%
“…Moreover, many programs appear to be treating these clinical outcomes as balancing measures, in that they want to confirm that reductions in antimicrobial use have not compromised important patient outcomes. For example, some authors have listed these outcomes under the heading of 'Programme safety' or 'Negative consequences' [24,54].…”
Section: Clinical Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Diversas estratégias têm sido propostas para combater a resistência microbiana no mundo, dentre elas destacam-se os Programas de Otimização de Uso de Antimicrobianos, que começaram a ser incorporados nos Serviços de Controle de Infecção Hospitalar. 3 A implementação do Programa de Otimização do Uso de Antimicrobianos requer um esforço multiprofissional e envolve uma série de intervenções específicas a fim de monitorar o uso de antimicrobianos e proporcionar um padrão de terapia baseada em evidência. Dentre os objetivos dos chamados programas de vigilância do uso de antimicrobianos "Antimicrobial stewardship" estão: melhorar o resultado para o paciente, garantir sua segurança, reduzir a velocidade de emergência da resistência microbiana e reduzir custos, promover a educação continuada e o feedback constante ao prescritor.…”
Section: Introductionunclassified